Електротермостимульована деполяризація металополімерних пар тертя стрічково-колодкових гальм бурових лебідок - Криштопа, Святослав; Прунько, І.; Журавльов, О. (КІНПАТРІ ЛТД, 2013)
The article is devoted to the task of decline of energy loading of metal-polymer pairs of friction of band-block brake of drilling hoist. The analysis of processes which take place with the components of polymeric materials at the change of the electric fields and at cooperation of areas of metal-polymer pairs friction of band-block brake is carried out. Thus there is reduction of wearing of working surfaces of friction protective straps of band-block brake of drilling hoist.
Elektrothermostimulated depolarization parts of areas of metal polymeric friction pairs of band-block brake of drilling hoists